Investigating the causes of delays at border posts: A focus on institutional and infrastructural factors at Beitbridge Border Post - Maredi, Lydia (Research of GSB, 2018)
Beitbridge is regarded as the busiest and the most inefficient border post in Sub-Saharan Africa due to its poor state of systems and infrastructure. It takes travellers more than two hours to cross the border on a normal day, and a minimum of two days during holidays. Trucks spend up to five days trying to get cleared and cars queue for kilometres from the immigration buildings. These cause problems of delays, corruption and revenue leakages at the border. This research investigated how institutional and infrastructural factors contribute to delays at the Beitbridge Border Post and identified possible solutions to these delays. Using the "border theory" as a theoretical framework, the research documented and focused on major issues around delays and problems at the Beitbridge Border Post, and possible solutions. Being an exploratory study, the research used an inductive qualitative approach to using primary and secondary data sources to understand issues that contribute to delays at the border post and to come up with a possible policy recommendation. The findings revealed that most institutional problems causing delays at the border are duplication of tasks between different agencies operating at the border post and resistance to procedures due to failure of following instructions by users. Infrastructural problems causing delays at the border include, amongst others, the usage of a single bridge that causes congestion and convergence of traffic at the gate; and the reason that there is no enough parking on both sides of the border. These findings support the border theory in terms of how borders impact people's daily lives.